2020
DOI: 10.1016/j.jimonfin.2020.102152
|View full text |Cite
|
Sign up to set email alerts
|

Credit intermediation and the transmission of macro-financial uncertainty: International evidence

Abstract: The responsibility for the working papers lies with the respective authors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
0
0
Order By: Relevance
“…Therefore, the impact of economic policy uncertainty on the manufacturing industry may be non-linear, and the direction of the impact may also change. Previous studies have confirmed that the impact of economic policy uncertainty on some macroeconomic variables often has temporal differences in direction; for example, Gächter [60] found that the dependence of uncertainty on economic activities depends on the transmission of countries, and global uncertainty shocks can have adverse nonlinear effects on the macroeconomic system; at the same time, Caggiano [61] found that the Canadian unemployment rate reacted more strongly to the impact of the uncertainty of American economic policy during the Canadian economic depression through empirical research. Similarly, Li [62] believed that the impact of economic policy uncertainty on financial stability and the green bond in the long and short run may be different; that is, the impact of economic policy uncertainty on macroeconomic variables is time-varying.…”
Section: Hypothesesmentioning
confidence: 90%
“…Therefore, the impact of economic policy uncertainty on the manufacturing industry may be non-linear, and the direction of the impact may also change. Previous studies have confirmed that the impact of economic policy uncertainty on some macroeconomic variables often has temporal differences in direction; for example, Gächter [60] found that the dependence of uncertainty on economic activities depends on the transmission of countries, and global uncertainty shocks can have adverse nonlinear effects on the macroeconomic system; at the same time, Caggiano [61] found that the Canadian unemployment rate reacted more strongly to the impact of the uncertainty of American economic policy during the Canadian economic depression through empirical research. Similarly, Li [62] believed that the impact of economic policy uncertainty on financial stability and the green bond in the long and short run may be different; that is, the impact of economic policy uncertainty on macroeconomic variables is time-varying.…”
Section: Hypothesesmentioning
confidence: 90%